ANALYSIS OF SAFETY RISK MANAGEMENT IMPLEMENTATION IN THE BOEING 737 - 300 ENGINE REPLACEMENT PROCESS AT PT. MULYA SEJAHTERA TECHNOLOGY: Analisis Penerapan Manajemen Resiko Keselamatan Pada Proses Penggantian Engine Boeing 737 - 300 di PT. Mulya Sejahtera technology - Verdi Eka Saputra; Iwan Engkus Kurniawan; Diding Sunardi (Jurnal Penelitian)
This study discusses the application of safety risk management in the process of engine replacement Boeing 737 – 300 at Hangar Hall E PT. Mulya Sejahtera Technology Bandung. The research method used is descriptive and qualitative, namely by using the HIRAM (Hazard Identification, Risk Assessment and Mitigation) method. The results showed that there were 9 hazards, with 3 hazards in the Med-High Acceptable category and 6 hazards in the Med Acceptable category. Mitigation is carried out by providing equipment, providing Personal Protective Equipment (PPE), repairing stairs to support maintenance work, providing appropriate lights, adjusting the use of roll cables (terminals), eyewash repairs, adjusting the contents of the first aid kit, and modifying the transit parts rack.